2005
DOI: 10.1111/j.1600-6143.2005.00798.x
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Long-Term Graft Survival Rates Between the First and Second Donor Kidney Transplanted-The Effect of a Longer Cold Ischaemic Time for the Second Kidney

Abstract: Prolonged cold ischaemic time (CIT) is associated with delayed initial graft function and may also have a negative impact on long-term graft outcome. We carried out a study comparing the long-term graft survival rates between those recipients who received the first of a pair of donor kidneys versus the recipient of the second graft.Adult kidney transplant recipients who received one of a pair of donor kidneys at our institution between 1989-1995 were included. All recipients received a cyclosporin based immuno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
24
3
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(37 citation statements)
references
References 16 publications
(39 reference statements)
8
24
3
2
Order By: Relevance
“…Prolonged cold ischemia time is associated with higher risks for DGF and may adversely affect graft outcome (14,15). However, our analysis found that in deceased donor transplants, total ischemia time of Ͼ18 hr was not associated with worse graft survival at 1-5 years when compared to total ischemia time of Ͻ12 hr (data not shown).…”
Section: Zero-antigen Mismatched and Six-antigen Mismatched Transplancontrasting
confidence: 49%
“…Prolonged cold ischemia time is associated with higher risks for DGF and may adversely affect graft outcome (14,15). However, our analysis found that in deceased donor transplants, total ischemia time of Ͼ18 hr was not associated with worse graft survival at 1-5 years when compared to total ischemia time of Ͻ12 hr (data not shown).…”
Section: Zero-antigen Mismatched and Six-antigen Mismatched Transplancontrasting
confidence: 49%
“…Univariate analysis shows that cold ischemic time is the independent factor that could correlate with long-term graft survival in our cohort, but using Cox regression model we found that this variable was not related to graft survival rate. Detrimental effect of increasing cold ischemia time on long-term graft survival has been proved in several other reports, for example, Giblin et al 28 compared the recipients of a first deceased donor transplanted and the recipient of the second donor kidney transplanted. The 5-and 10-year survival was 72 and 55% for the first kidney transplanted, respectively, compared with 65 and 40% for the second kidney transplanted.…”
Section: Discussionmentioning
confidence: 99%
“…The vast majority of late failures are attributable to chronic allograft nephropathy (CAN), recently reclassified as interstitial fibrosis and tubular atrophy with unknown etiology. [3][4][5][6] The clinical course of CAN is characterized by a progressive deterioration in renal function, manifested by increasing renal hypertension and proteinuria. Presently, no specific treatment is available for chronic rejection in clinical transplantation despite a number of successful approaches in animal models, including the use of macrophage inhibitors, angiotensin converting enzyme inhibitors, and endothelin A receptor antagonists.…”
mentioning
confidence: 99%